2010
DOI: 10.1111/j.1751-5823.2010.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effect of Data Collection Mode on Measurement

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(81 citation statements)
references
References 18 publications
0
78
0
1
Order By: Relevance
“…13 To the best of our knowledge, there is no study on effects of changing data collection modes on task composition. From the literature on method changes in general (Roberts 2007;Jäckle et al 2008), we do not expect relevant differences in the answering behaviour (measurement error); job tasks as surveyed here are not sensitive questions and thus should not provoke social desirability. All five rounds are probability samples of the German active labor force and we use comparable samples of respondents, i.e.…”
Section: Task and Skill Itemsmentioning
confidence: 74%
“…13 To the best of our knowledge, there is no study on effects of changing data collection modes on task composition. From the literature on method changes in general (Roberts 2007;Jäckle et al 2008), we do not expect relevant differences in the answering behaviour (measurement error); job tasks as surveyed here are not sensitive questions and thus should not provoke social desirability. All five rounds are probability samples of the German active labor force and we use comparable samples of respondents, i.e.…”
Section: Task and Skill Itemsmentioning
confidence: 74%
“…Only hearing the question and not being able to see the interviewer during a telephone interview may also make the respondent more fatigued. This may result in more off the cuff responses (satisficing) in telephone interviews (Holbrook et al, 2003), though Jäckle et al (2010) found no evidence of satisficing in their study of modes in the European Social Survey. In addition, a person is more likely to be multi-tasking during a telephone interview when the interviewer cannot see them.…”
Section: Direction Of Mode Effectsmentioning
confidence: 94%
“…There is now a wealth of research investigating the size and causes of these effects (de Leeuw, 2005;Dillman, 2000;Dillman & Tarnai, 1988;Holbrook et al, 2003;Jäckle et al, 2010;Kreuter, Presser, & Tourangeau, 2008;Lynn, 1998;Tourangeau & Smith, 1996). Overall, existing reviews comparing face-to-face and telephone (de Leeuw, 2005;de Leeuw & van der Zouwen, 1988) indicate that there appear to be relatively few differences between the two interviewer-administered modes of telephone and face-to-face.…”
Section: Size Of Mode Effectsmentioning
confidence: 99%
See 2 more Smart Citations